THYROID FUNCTION TEST IN SEVERE COVID-19 PATIENTS IN HOSPITAL SUNGAI BULOH - Atikah, Sharifah Khairul; Yunus, Zuhaira Hayati; Yusoff, Nur Amalina; Yusoff, Yusniza (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION COVID-19 may have widespread effects throughout the body, including the endocrine glands, which can be impaired by different mechanisms. Several recent reports have described the onset of thyroid dysfunction in previously healthy patients diagnosed with COVID-19. Thus, we aimed to describe the pattern of abnormal thyroid function tests (TFTs) in severe COVID-19 patients in Hospital Sungai Buloh. METHODOLOGY Thyroid stimulating hormone (TSH) and free thyroxine (fT4) were received from all critical care wards catering for severe COVID-19 adult patients (Clinically Stage 4 and 5) from December 2020 till June 2021. It was retrospectively reviewed in Laboratory Information System (LIS) with exclusion of thyroid disease, pregnancy or immunotherapy. SARS-CoV-2 infection was confirmed by RT-PCR of nasopharyngeal swab samples and severity classification was based on the Malaysia MOH guideline. Analysis of TFT was performed on Siemens Atellica using chemiluminescent immunoassay RESULTS From 184 TFT results analysed, about 120 patients (65%) had abnormal thyroid function, of which 62.5% had low TSH level with normal fT4 and 15.8% had low TSH with high fT4. This indicated that abnormal TFT is common among COVID-19 patients, with low TSH being most common. However, we are unable to exclude steroid use as a cause of low TSH levels as steroid is one of main treatments prescribed in severe COVID-19 cases. CONCLUSION There was a high proportion of abnormal TFT in severe COVID-19 patients even in the absence of pre-existing thyroid conditions. For clinicians directly involved in treating these patients, they need to be vigilant in interpreting thyroid function abnormality in COVID-19 infection.